Aerobic exercise in children with oxidative phosphorylation defects - Luuk Schreuder; Gera Peters; Ria Nijhuis-van der Sanden; Eva Morava (MDPI AG, 2010)
Fatigue and exercise intolerance are symptoms in children with metabolic myopathy. Frequently this is combined with muscle pain in children with mitochondrial myopathy. Offering therapeutic advice remains challenging in this patient group. Here we describe five children above the age of four years, with normal intelligence, myopathy, exercise intolerance, motor developmental delay, and fatigue, who were diagnosed with a mitochondrial dysfunction. Based on the positive experience of condition training in adults with mitochondrial disease and inactivity, aerobic exercise training was advised for all the children. Because of the lack of clear protocols for individualized mitochondrial myopathies, regular training was initiated. The Movement Assessment Battery of Children, the Jamar dynamometer for grip force, and the Bruce protocol treadmill test were applied for evaluation. No patient showed significant disease progression on a weekly scheme of strength training or on aerobic training during periods varying between 6 and 18 months. Only one out of the five patients has shown an improvement after a period of structured, aerobic training, demonstrating good compliance and motivation over the course of 18 months. Some patients developed severe muscle pain after explosive exercise. Even in a relatively homogenous, intelligent group of patients and motivated parents, we could not reach full compliance. With our case studies, we would like to draw attention to the importance and pitfalls of movement therapy in children with mitochondrial disease.